A newly developed tracheal tube offering 'pressurised sealing' outperforms currently available tubes in preventing cuff leakage: A benchtop study. Issue 7 (July 2017) - Spapen, Herbert D.; Suys, Emiel; Diltoer, Marc; Stiers, Wim; Desmet, Geert; Honoré, Patrick M.
Abstract : BACKGROUND: No currently used tracheal tube offers full protection against aspiration of oropharyngeal secretions into the lower airways. OBJECTIVE: We developed a tracheal tube equipped with two polyvinylchloride (PVC) cuffs with a supplementary port opening between the cuffs through which a continuous positive pressure of 5 cmH2 O is provided [double-cuffed PVC (PVCdc )]. We compared this PVCdc with four different cuff types (cylindrical PVC, conical PVC, cylindrical polyurethane and conical polyurethane). DESIGN: A comparison study using an in-vitro benchtop model of an artificial rigid trachea. INTERVENTIONS: Tracheal tubes were placed in the artificial trachea. Both cuffs were kept inflated at 25 cmH2 O. Total 3 ml dyed water was placed above the cuff and leakage recorded under static and dynamic [5 cmH2 O positive end-expiratory pressure (PEEP) alone or positive pressure ventilation plus 5 cmH2 O PEEP] conditions. At the end of the dynamic experiments, PEEP was zeroed (PEEP alone) or the tracheal tubes were disconnected from the ventilator (positive pressure ventilation plus PEEP). RESULTS: In the static model, leakage flows [medians (range)] were 9.8 (6.2 to 20) for the cylindrical PVC, 1.3 (0.2 to 3.8) for the conical PVC, 0.03 (0.007 to 0.1) for the cylindrical polyurethane, 0.04 (0.003 to 0.2) for the conical polyurethane and 0.0 (0.0 to 0.0) ml min −1 for the PVCdc cuff ( P < 0.001, PVCdc vs. all other cuffs). In the dynamic setting, no leakage was detected for up to 60 min with any of the cuffs studied. Loss of PEEP or tracheal tube disconnection resulted in dye inflow alongside all cuffs except for the PVCdc ( P < 0.001, PVCdc vs. all other cuffs). CONCLUSION: A 'pressure seal' incorporated in a double-cuffed tracheal tube prevented fluid passage into the lower airways. Clinically, this may translate into absence of inflow of bacteriologically contaminated secretions into the lungs and thus a lower incidence of ventilator-associated infection.